(untitled) (Revista de Ciências Agroveterinárias, 2015)
Efficient plant production in recipients requires appropriate knowledge of the substrate characteristics that have important role in supporting plant root systems and offering suitable moisture for their growth. The primary source of the substrate defines different characteristics to the growth media, limiting its successful employment in crop water management. In order to indicate suitable physical substrate attributes for capillarity irrigation, the objective of this study was to evaluate the effects of two particle size distribution (fine and coarse) of coconut and pine bark substrates on physical attributes related to water retention. For both of analyzed substrates, poremeter and particle size distribution analysis methods were employed, adding gravitational particle separation for the coconut material. The results have indicated that the coconut substrate with coarse particles distribution presented deficiency for watering processes by capillary rise due to a higher porosity caused by the fiber constitution. Fine substrates, with smaller average particle size and lower percentage of particle fibers, showed more suitability for water storage processes and, consequently, capillary rise processes. The fine coconut substrate presented higher aeration with high water retention capacity.